Effect of BaSnO3 on structural and electrical properties of lead free Na0.5Bi0.5TiO3 ceramic solid solution. (19th August 2021) - Sasikumar, S; Fan, Huiqing; Wang, Weijia; Thirumalaisamy, T K; Saravanakumar, S; Diana, P; Sivaganesh, D
Abstract: A series of novel lead-free (1-x)(Na0.5 Bi0.5 )TiO3 –xBaSnO3, (x = 0.00, 0.05, 0.10) ceramics were fabricated by solid-state air sintering route and their dielectric and microstructural properties were studied. Various experimental methods to characterize the fabricated ceramics such as PXRD, Raman spectra, SEM-EDS, UV-visible and dielectric studies. All the ceramics were crystallized by rhombohedral symmetry using PXRD and Rietveld profile refinement technique. The experimental atomic charge density distribution studies were performed and the bonding characteristics were analyzed. With increase of BSN content, the average grain size decreased and was characterized by scanning electron microscopy (SEM) technique. Energy dispersive x-ray (EDS) spectra indicate the presence elements and the diffusion of BSN into the rhombohedral phase of NBT matrix. The optical bandgap was determined by UV-Visible spectra and the values are found to be 3.05, 3.10 and 3.12 eV. The temperature dependence of dielectric constant ( ε ) provides evidence for dielectric anomalous behaviour in the higher doping of BSN concentration.